Desulfurization use of marble wastes - Tosun, Yıldırım İsmail (Makine Mühendisliği Bölümü, Karadeniz Teknik Üniversitesi, Trabzon, 1996)
Desulfurization of coalhas firstly applied for the flue gas in coke production and in fluidized bed combustion systems after coal burning. In recent, the desulfurization methods have significantly been progressed by founded the desulfurizationplants in thermal power stations. However, small scale operationof desulfurizationplants ca not be practical. Solid basic filters, especially using marble waste developed for sulfur dioxide holdup, may be economicalin small scale burning systems. In this study, few types of solid basic filters were used in cold medium following the combustion of coal samples and at different burning temperatures in the combustion chamber. Finally, the effects of variables on emmision as the percentages of sulfur dioxide holdup were determined.
Keywords: desulfurization, marble wastes, solid filters